2007
DOI: 10.1186/1471-2431-7-27
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of sucrose and/or pacifier as analgesia for infants receiving venipuncture in a pediatric emergency department

Abstract: Background: Although sucrose has been accepted as an effective analgesic agent for procedural pain in neonates, previous studies are largely in the NICU population using the procedure of heel lance. This is the first report of the effect of sucrose, pacifier or the combination thereof for the procedural pain of venipuncture in infants in the pediatric emergency department population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 25 publications
1
60
1
10
Order By: Relevance
“…Despite the availability of effective topical analgesic agents for urinary catheterization, which is known to be pain and anxiety provoking, 27,28 60% of physicians in our study reported providing no analgesia for pediatric urinary catheterizations. Similarly, although IV insertion is known to cause moderate pain in infants and many options exist to limit this pain, 15,20,21,25,29 only half of physicians reported that they ''often or always'' used analgesia for venipuncture. LP is another procedure for which multiple effective analgesic interventions exist and are recommended in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of effective topical analgesic agents for urinary catheterization, which is known to be pain and anxiety provoking, 27,28 60% of physicians in our study reported providing no analgesia for pediatric urinary catheterizations. Similarly, although IV insertion is known to cause moderate pain in infants and many options exist to limit this pain, 15,20,21,25,29 only half of physicians reported that they ''often or always'' used analgesia for venipuncture. LP is another procedure for which multiple effective analgesic interventions exist and are recommended in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…ten is the maximum score indicating severe pain and a score < 2 generally indicates absence of pain 22,23 . A FlACC score higher than 4 is considered as indicator of moderate pain 24 .…”
Section: Data Collectionmentioning
confidence: 99%
“…[51][52][53][54] In addition, a 50% glucose solution was no more effective than water during circumcision, 55 and a single dose of sucrose failed to significantly reduce crying in older infants undergoing urethral catheterization 56 and venepuncture. 57 The reduced effectiveness of sweet solutions in these more invasive procedures of relatively long duration may be due to the shortlasting effects of a single dose given 2 minutes before the procedures. Effects may not be sustained over prolonged procedures, especially in infants beyond the newborn period.…”
Section: Human Model Studiesmentioning
confidence: 99%